The exegetical terminology of Akkadian commentaries - Gabbay, Uri, 1975- (Culture and History of the Ancient Near East, 2016)
In The Exegetical Terminology of Akkadian Commentaries Uri Gabbay offers the first detailed study of the well-developed set of technical terms found in ancient Mesopotamian commentaries. Understanding the hermeneutical function of these terms is essential for reconstructing the ancient Mesopotamian exegetical tradition. Using the exegetical terminology attested in the large corpus of Akkadian commentaries from the first millennium BCE, the book addresses the hermeneutics of the commentaries, investigates the scholastic environment in which they were composed, and considers the relationship between the terminology of commentaries and the divine authority of the texts they elucidate. The book concludes with a comparative study that traces links between the terminology used in Akkadian commentaries and that used in early Hebrew exegesis.